MEMBANGUN MEDIA SERVER DENGAN MENGGUNAKAN RASPBERRY Pi UNTUK PENGOLAHAN DATA AUDIO VIDEO - Yudo, Bondan Prawiro; Lestari, Uning; Hamzah, Amir (Jurnal Script, 2014)
ABSTRACTThe development of computer technology at the present time has become part of everyday life. Computer technology has an important role in the processing of audio and video data. Audio and video are part related to multimedia and commonly used in everyday life. Media server that functions as a service provider to perform the data processing of audio and video. Data processing of audio and video by using the media server can be optimized and used more efficiently. Media servers required innovations in functionality as a data processor. The information presented media server more attractive, so that individual and overall user has more appeal to the presentation of audio and video data. The media server built for the processing of audio and video data can be used by individuals or groups that are tailored to their needs.Build a media server using the Raspberry Pi has the concept of using an open source operating system Linux. The media server uses application XBMC (X-Box Media Centre) as a media player which is a standard for the media server. The media server built allows for the use of peripherals as input and outputs to support the operation of the media server.Key words : Media server, Raspberry Pi, XBMC